Determinants of social norms and support services for the entrepreneurial spirit of rural farmers in sub-Saharan Africa: The case of Borgou in Benin - (:unkn) unknown (My University, 2023)
The peasant entrepreneur evolves in a very particular context that influences his entrepreneurial spirit and capacities. The objective of this study is to identify the social determinants of the entrepreneurial spirit of rural farmers. The study conducted on 293 farmers in Borgou shows that social norms, the family environment, the personal attributes of the farmer, and the mechanisms put in place to promote the development of agro-economic activities are all factors that influence either positively or negatively the entrepreneurial spirit and skills of farmers.
Keywords: African Research